WAYANG SIMULATOR USING AUGMENTED REALITY AS A WAYANG LEARNING MEDIUM FOR STUDENTS IN SMP SEMEN GRESIK - Doni Setio Pambudi (Fakultas Seni Rupa dan Desain ITB, 2019)
Wayang is one of Indonesia's most prominent traditional arts among many other cultural works. However, at present the existence of wayang in general has been neglected, marked by the decreasing number of youngsters who are interested in wayang preservation. This is because there is no media that can be easily accessed to learn wayang. An application is developed by utilizing Augmented Reality. This has become a medium to learn wayang. This application will create a new image in wayang learning especially for children. Wayang in this program is made from cardboard in the form of frames and is given an identifier in the form of AR Tags which is then scanned using a webcam. Wayang simulator is the future of wayang learning in Indonesia.